1991
DOI: 10.2307/1242711
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Technological Change and Institutional Reform on Production Growth in Chinese Agriculture

Abstract: Recent rapid agricultural production growth in Chinese agriculture could be attributed to an increase in inputs, technological change, and institutional reform. An accounting approach was used to separate the relative contribution of these three factors. Institutional change, like the introduction of the household production responsibility system, has contributed to past growth in production. However, technological change is crucial to furthering production growth because of the limited potential for significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
201
0
6

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 349 publications
(217 citation statements)
references
References 5 publications
7
201
0
6
Order By: Relevance
“…On the other hand, Jeanneney and Kpodar (2011) studied the developing countries and Sub-Saharan African countries and finally concluded that there is a negative relationship between trade liberalization and the income of poor people which create the poverty and poverty gap. Moreover, Freund and Bolaky (2008) examined that trade policy leads to increased poverty whereas several other studies, for example, Fan (1991) and Lin (1992) revealed the opposite result using endogenous threshold regression model happening in China after its economy has been experiencing some degree of globalization. Naranpanawa et al (2011) made a case study on Sri-Lanka using computable general equilibrium which shows trade openness and poverty relationship and found that trade openness increases the poverty in Sri-Lanka which creates the gap between rich and poor.…”
Section: Trade Openness and Povertymentioning
confidence: 99%
“…On the other hand, Jeanneney and Kpodar (2011) studied the developing countries and Sub-Saharan African countries and finally concluded that there is a negative relationship between trade liberalization and the income of poor people which create the poverty and poverty gap. Moreover, Freund and Bolaky (2008) examined that trade policy leads to increased poverty whereas several other studies, for example, Fan (1991) and Lin (1992) revealed the opposite result using endogenous threshold regression model happening in China after its economy has been experiencing some degree of globalization. Naranpanawa et al (2011) made a case study on Sri-Lanka using computable general equilibrium which shows trade openness and poverty relationship and found that trade openness increases the poverty in Sri-Lanka which creates the gap between rich and poor.…”
Section: Trade Openness and Povertymentioning
confidence: 99%
“…If the expected results have not been gained, the elasticity coefficient will be modified. The randomness of the contribution rate of science and technology progress will increase because of this characteristic [6,7]. The regression analysis is accepted with taking into account of every factor in this paper.…”
Section: The Determination Of Standard Labormentioning
confidence: 99%
“…The function is approximated by the quasi -translog functional form, proposed by Fan (1991) and Karagiannis and Tzouvelekas (2001 is an independently and identically distributed one-sided random error term representing the stochastic shortfall of the ith farm output from its production frontier due to the existence of technical inefficiency (i.e., farm -specific outputoriented technical inefficiency). It is further assume d that the two error terms are independently distributed from each other.…”
Section: Empirical Model 41 Frontier Production Functionmentioning
confidence: 99%